Preparation and Structural Characterization of L-Arginine-selenic Acid Addition Compound - Liu, Anjun; Sun, Kezhuang; Zhu, Zhen-Yuan; Fan, Yanli (Asian Journal of Chemistry, 2012)
Seleno-arginine was synthesized using arginine and selenium dioxide and its conventionally chemophysical properties were analyzed. The structure of the product was determined by high performance liquid chromatography, Fourier transform spectrometer, mass spectra and nuclear magnetic resonance spectroscopy.